The Operation Challenges: A PEST Analysis of Taiwan’s Renewable Energy Promotion - DING, CHENG-YU (2017)
With limited space and resources, Taiwan is currently facing conundrum with readjusting its energy portfolio towards sustainability. This paper examines the implementation of Taiwan’s Renewable Energy Development Act (REDA) towards the nuclear-free commitment. At first, the pressures such as energy deficiency and nuclear concerns forced Taiwan to come up with new plan for its energy mix. To promote renewable energy usage, REDA was facilitated in 2009. Along with the constraint of nuclear power abolishment by 2025, the act has become the centre of public attention. PEST analysis is applied for identifying the influential factors in far external environment and putting them into themes in regard to the REDA policy implementation. The objective of the dissertation is to identify the companies’ and governments’ strategic foci due to the policy implementation. Recommendations are provided to resultant concerns and opportunities for future consideration.